TREN SUMBER BELAJAR PAI MEDIA MASSA DAN TANTANGANNYA DI ERA MODERN - Muhammad Helmi (Program Studi PAI STAI Al Falah Banjarbaru, 2020)
The large number of mass media now circulating in society that can be accessed quickly and easily has caused other media such as newspapers to experience a shift in interest. In learning, learning resources become a supporting force for learning activities, including support systems, materials and learning environments. The criteria for selecting learning resources are suitability to the learning objectives, availability of local resources, whether there are sufficient funds, personnel and facilities to provide the learning resources, and factors relating to the practicality of the learning resources used. This type of research uses a literature review with a qualitative approach. One of the results of collecting literacy is mass media as a means of disseminating information to the public. In this case, internet usage in the modern era is increasing, which can be seen from the survey that Indonesian internet users increased by 10.12% in 2018 compared to the previous year. Internet users reached 171.17 million out of a population of 264.16 million people. This is a challenge for society in the modern era to be able to process information first before disseminating it. So it can ward off hoax news everywhere.